Evaluation of Laboratory Findings, Clinical Features and Rates of Diagnosis of Patients Admitted to Outpatient Clinic of Pediatric Neurology with Neuromuscular Manifestations - Tuğçe Aksu Uzunhan; Biray Ertürk; Pelin Özyavuz Çubuk; Bülent Uyanık; Akif Ayaz; Onur Akan; Taha Reşid Özdemir (Galenos Publishing House, 2020)
INTRODUCTION: Our aim is to evaluate how many patients with neuromuscular manifestations get a definite diagnosis and which methods are used in the pathway to diagnosis as well as to assess patient characteristics. METHODS: Patients aged 0-18 years old with neuromuscular manifestations (e.g., weakness, hypotonia, creatine kinase elevation) who were admitted to Okmeydani Training and Research Hospital between January 2017 and July 2019 were included. Retrospectively, patient demographics, clinical signs, laboratory tests, diagnoses, clinical follow-up were recorded. RESULTS: Forty-five patients aged 67.8+-59.6 months were included in the study. Thirteen (29%) patients were female, and 32 (71%) were male. Creatine kinase levels were increased in 26 (58%) patients (median: 3211 IU/L). Twenty-four patients underwent electromyography; seven patients had neuropathy and nine patients muscular pathologies. Three (0.07%) patients underwent muscle biopsy and had nonspecific myopathic changes. Twenty-six (58%) patients out of 45 had a definite diagnosis, and 21 of these diagnoses were genetically confirmed. Seven patients had been subjected to next generation sequencing, and five of these were diagnosed with dystrophinopathy, hypokalemic periodic paralysis, mental retardation autosomal dominant type 9, Ullrich muscular dystrophy, and calpainopathy. Altogether, the most common diagnoses were dystrophinopathy, spinal muscular atrophy, and chronic inflammatory demyelinating polyneuropathy. DISCUSSION AND CONCLUSION: After a patient history is taken, a physical examination is conducted, and serum creatine kinase levels are measured, establishment of diagnosis is possible through targeted genetic tests for diseases like dystrophinopathy. However, for patients who cannot be diagnosed with this approach, neuromuscular panels and whole exome sequencing can provide a diagnosis.